BlueFinder : recommending Wikipedia links using DBpedia properties - Torres, Diego
DBpedia knowledge base has been built from data extracted from Wikipedia. However, many existing relations among resources in DBpedia are missing links among articles from Wikipedia. In some cases, adding these links into Wikipedia will enrich Wikipedia content and therefore will enable bet- ter navigation. In previous work, we proposed PIA algorithm that predicts the best link to connect two articles in Wikipedia corresponding to those related by a semantic property in DB- pedia and respecting the Wikipedia convention. PIA calcu- lates this link as a path query. After introducing PIA results in Wikipedia, most of them were accepted by the Wikipedia community. However, some were rejected because PIA pre- dicts path queries that are too general. In this paper, we report the BlueFinder collaborative filtering algorithm that fixes PIA miscalculation. It is sensible to the specificity of the resource types. According to the conducted experimentation we found out that BlueFinder is a better solution than PIA because it solves more cases with a better recall.